THE IMPLEMENTATION OF WOMEN'S EMPOWERMENT PROGRAM IN REALIZING GENDER EQUALITY - Fransiska Theresia Kune; Willy Tri Hardianto; M. Rifa’i (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Women’s empowerment in realizing gender equality is one of the responsibilities of the Government and is conducted by government agencies, both central and regional. Problems which still occur to women today are the cases of violence and discrimination. This research was conducted by using descriptive qualitative research, the results of the study stated that there were the implementation of the women's empowerment program in realizing gender equality in Surabaya proven by the program named Gender Equality and Women's Empowerment. It provided several activities such as: Capacity Building of the Women's Organizational Association (GOW) at some sectors such as Politics, Economics, Social and Culture, Independent Business Incubation for productive age women, Implementation of Gender Socialization, Creative Houses for Low-Income Communities (MBR) especially for the productive age women who do not have a business yet by obtaining material on Entrepreneurship, Empowerment of UMKM in Surabaya by making masks and APD during the pandemic, and also Urban Farming for the community through the use of vacant land.